Prevedeni (mikro)svetovi: Roman Vojak s cvetlico Nándorja Giona v slovenskem, nemškem in srbskem prevodu - Futó Horváth, Hargita; Rudaš, Jutka; Hózsa, Éva (Slavia Centralis, 2020)
TRANSLATED (MICRO) WORLDS: THE NOVEL SOLDIER-WITH-FLOWER BY NÁNDOR GION IN SLOVENE, GERMAN AND SERBIAN TRANSLATIONSThe lexicon of the novel Soldier-With-Flower by the Hungarian author Nándor Gion presents rich historical, cultural-historical, ethnological and anthropological material. The current research focuses above all on the aspects of translations into Serbian, German, and Slovene. The analysis focuses on the translation of culturally specific details with attention to the notion that a translation is not merely a function of grammar and vocabulary of both languages, but an intercultural communication, i.e., a cultural exchange. In the intercultural translation any aspect of reality can be “translated” by implying various translation strategies. A translation is a carrier of the source culture and as such should be considered a significant element of intercultural communication. As the culture is an organized system of symbols, the carriers of meanings, it is on the one hand a "model of reality" and on the other a "model of truth" (Iser).
Keywords: cultural reality; intercultural communication; cultural codes; Nándor Gion; translation strategy